Long-term-video monitoring EEG and 18F-FDG-PET are useful tools to detect residual disease activity in anti-LGI1-Abs encephalitis: A case report - Cornacchini, Sara; Farina, Antonio; Contento, Margherita; Berti, Valentina; Biggi, Martina; Barilaro, Alessandro; Massacesi, Luca; Damato, Valentina; Rosati, Eleonora (Frontiers in Neurology, 2022)
Background The use of CD20-depleting monoclonal antibodies has shown to improve the long-term outcome of patients with anti-leucine-rich glioma-inactivated protein 1 antibodies (anti-LGI1-Abs) encephalitis after first-line immunotherapy, but currently predictive markers of treatment response and disease activity are lacking. Case presentation A 75-year-old man presented cognitive impairment and faciobrachial dystonic seizures (FBDS), with mild abnormalities at electroencephalography (EEG), normal brain magnetic resonance and cerebrospinal fluid (CSF) analysis. Anti-LGI1-Abs were detected in serum and CSF, and corticosteroids and intravenous immunoglobulins were administered. Despite partial cognitive improvement, 18F-fluoridesoxyglucose-positron emission tomography (18F-FDG-PET) showed the persistence of temporo-mesial hypermetabolism, and FBDS were still detected by long-term monitoring video EEG (LTMV EEG). Rituximab was therefore administered with FBDS disappearance, further cognitive improvement, and resolution of 18F-FDG-PET temporo-mesial hypermetabolism. Conclusions Our experience supports the use of 18F-FDG-PET and LTMVEEG as useful tools to measure disease activity, evaluate treatment response and guide therapeutic decisions in the long-term management of anti-LGI1-antibody encephalitis.